E-mail processing using data mining techniques - Villa Monte, Augusto
A proposal to use data mining techniques to analyze e-mails corresponding to courses carried out through a distance education plat- form is made. The purpose of this type of analyses is determining which are the groups of relevant words that allow establishing communication topics of interest. Even though this new information can have various applications, they all involve an improvement in student service. The method proposed has been applied to the e-mails of the PACENI Project (Support Project for Improving First-Year Teaching in Courses of Studies in Exact and Natural Sciences, Economic Science and Computer Science) with satisfactory results.